Politik Hukum Hak Uji Materiil AD/ART Partai Politik dalam Putusan Mahkamah Agung Nomor 39 P/HUM/202 - Alendra Nauval Mufti Rayhan; Salsabil Aqila Tasnim; Muhammad Al Fasya (Tapis: Jurnal Penelitian Ilmiah, 2026)
This study examines the legal policy underlying the material judicial review of the Articles of Association and Bylaws (AD/ART) of political parties in the Supreme Court Decision No. 39 P/HUM/2021. The issue is important because the position of political party AD/ART raises theoretical debates regarding the scope of statutory regulations and the authority of the Supreme Court in judicial review, while practically affecting internal party democracy and the protection of party members’ rights. Previous studies generally focus on the authority of the Supreme Court or disputes within political parties, whereas this research specifically analyses the legal policy behind the limitation of judicial review objects concerning political party AD/ART.This research employs a normative juridical method using statutory, conceptual, and case approaches. Primary legal materials include Supreme Court Decision No. 39 P/HUM/2021, Law No. 12 of 2011 on the Formation of Laws and Regulations, and Law No. 2 of 2011 on Political Parties, supported by secondary legal materials from books and scientific journals.The study finds that the Supreme Court adopted a formalistic interpretation of statutory regulations and declared the petition inadmissible because political party AD/ART do not possess generally binding legal force. The decision reflects a legal policy aimed at maintaining legal certainty regarding the limits of material judicial review objects. However, the ruling also indicates the need for a clearer legal mechanism to supervise internal political party norms that have broader public implications within a democratic system.